Relative heart size in two rodent species increases with elevation: reviving Hesse's rule. (30th June 2014) - Müller, Jörg; Bässler, Claus; Essbauer, Sandra; Schex, Susanne; Müller, Dennis W.H.; Opgenoorth, Lars; Brandl, Roland; McGeoch, Melodie
Abstract Aim We assessed the phenotypic responses of body size and organ weights of two small rodent species (Myodes glareolus and Apodemus flavicollis) to elevation, a surrogate for temperature and other environmental conditions. We expected not only an increase in body size (Bergmann's rule), but also an increase in relative heart weight with increasing elevation (Hesse's rule). Location The Bohemian Forest, south‐eastern Germany. Methods We measured body length, body mass, and mass of the heart, lung, liver, kidneys and spleen of 386 adult specimens (188 of A flavicollis and 198 of M. glareolus) from 28 localities at 300–1450 m a.s.l., and also recorded the number of ectoparasites. We analysed body length using linear mixed models, with site as a random factor and species, sex, population density and elevation as fixed factors, and included all two‐way interactions between species and the remaining fixed variables. For the organ masses, we included body length and body mass in the calculations to account for allometric variation of organ mass with body size. For a subset of individuals, we sequenced the mitochondrial D‐loop to analyse genetic variation along the elevational gradient. Results For both species, we found no support for Bergmann's rule. The body size of A. flavicollis even decreased with elevation. In contrast, the relative heart weight of both species significantly increased with elevation, thereby supporting Hesse's rule. Lung mass also increased with elevation. The mass of other internal organs showed no such consistent relationship with elevation. Neither species showed genetic differentiation across the elevational gradient. Main conclusions Our results suggest that both rodent species respond to increasing elevation by decreasing overall energy expenditure and by increasing overall aerobic capacity. In the context of climate change, our results indicate that biogeographers should pay more attention to the potential significance of genetic and/or phenotypic plasticity of relative organ mass to environmental heterogeneity.